The Essentials of Negotiation / Business Literacy for HR Professionals (Harvard Business School Press, 2005)
This practical tool includes tips and tools that will help HR professionals become effective and influential negotiators in their firms. Introduction, Negotiation and the HR Professional, The HR Professional as Negotiation Agent, Types of Negotiation, Types of Negotiation, The Importance of Relationships, Four Key Concepts, Preparing for a Negotiation, Negotiation Strategies, Frequently Asked Tactical Questions, Manipulative Negotiation Ploys, Barriers to Agreement, Mental Errors, Negotiations with Job Seekers and Employees, Negotiation with your Boss and Peer Managers and Other Senior Executives, Negotiations with Vendors and Consultants, Negotiations with Labor Unions, Negotiation over Legal Disputes, Negotiations Related to Mergers and Acquisitions, Making Negotiation a Core Capability, Sharpening your Skills and Benefiting Your Company, Notes, Glossary, Index.